Application of statistical methods in forecasting for spare elements demand - Kalev, Krasimir (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The problem of predicting the demand for spare elements is extremely important for continuous operation of machines. It is necessary to know when and how much to order. To calculate and ensure the availability of spare elements, appropriate mathematical models should be applied. The statistical method for predicting spare elements demand is considered in this paper. The study shows how to use a demand forecasting technique for determining the expected number of spare elements. Some of the results are given by engineering software.